ROUTLEDGE HANDBOOK OF MOBILE TECHNOLOGY, SOCIAL MEDIA AND THE OUTDOORS - Beames, Simon; Maher, Patrick T. ([S.l.] : ROUTLEDGE, 2024)
This is the first book to explore the numerous ways in which mobile technologies and social media are influencing our outdoor experiences. Across the fields of outdoor education, outdoor recreation and leisure, and nature-based tourism, the book considers how practices within each of those domains are being influenced by dramatically shifting interactions between technology, humans, the natural world, and wider society. Drawing on cutting-edge research by leading scholars from around the world and exploring key concepts and theory, as well as developments in professional practice, the book explains how digital technology and media are no longer separate from typical human and social activity. Instead, the broader field of outdoor studies can be viewed as a world of intertwined socio-technical assemblages that need to be understood in more diverse ways. The book offers a full-spectrum view of this profound shift in our engagement with the world around us by presenting new work on subjects including networked spaces in residential outdoor education, digital competencies for outdoor educators, the use of social media in climbing communities, and the impact of digital technologies on experiences of adventure tourism. This is essential reading for anybody with an interest in outdoor studies, outdoor education, adventure education, leisure studies, tourism, environmental studies, environmental education, or science, technology, and society studies.
Keywords: Outdoor education; Outdoor recreation; Tourism -- Information technology; Mobile communication systems; Social media; SPORTS & RECREATION / Sociology of Sports